A Comparative Study of the in vivo Distribution of 32P-Polyphosphates and 32P-Orthophosphate - Anghileri, Leopoldo J.; Miller, Esther S. (Nuklearmedizin - NuclearMedicine, 1972)
The distribution of 32P-polyphosphates (lineal and cross-linked) and 32Porthophosphate in normal and tumor bearing animals has been studied. Differences between the cross-linked and the lineal form are related to a different degree of susceptibility to the hydrolysis by the phosphatases. In contrast to orthophosphate, the polyphosphates showed a lower accumulation in soft tissues which gives an advantageous reduction of the total body radiation dose.